Tanggung Jawab Pengusaha Terhadap Pekerja Upah Harian - Solissa, Harold Imanuel; Pattipawae, Dezonda Rosiana; Matitaputty, Merlien Irene (CAPITAN: Constitutional Law & Administrative Law Review, 2025)
Daily wage employment is a common form of employment, particularly in the informal and labor-intensive sectors. However, in practice, daily wage workers are often in a legally and economically vulnerable position. Uncertain employment status, minimal legal protection, and limited access to basic labor rights are fundamental issues. Therefore, it is important to examine the legal responsibilities of employers towards daily wage workers. Based on the description above, the issues to be discussed are: what are the forms of employer responsibility towards daily wage workers and what are the legal consequences if employers fail to pay daily wage workers. The method used to analyze and discuss this issue is normative. The results of this study indicate that, legally, employers have an obligation to guarantee the rights of daily wage workers, including providing a living wage, occupational safety and health, working hours according to regulations, and participation in social security programs. However, in practice, many employers still fail to fulfill these obligations optimally due to weak supervision, poor legal understanding, and a lack of enforcement of sanctions. Therefore, it is necessary to strengthen the labor inspection system, increase legal education for employers and workers, and update policies that are more responsive to the protection of daily workers.